RNA sequencing of surface mucus producing cells captured with Laser Microdissection and Pressure Catapulting in mouse stomachs infected with Helicobacter pylori Sydney Strain 1 - Erhardsson, Mattias; Lindén, Sara; Sharba, Sinan; Santos, Licínia (University of Gothenburg, 2026)
This RNA sequencing (RNAseq) data comes from mouse strain C57/BL6 gastric surface mucus cells, also known as foveolar cells.

5 mice were non-infected controls, 5 were infected with Helicobacter Pylori strain SS1 14 days prior to harvest, and another 5 were also infected with Helicobacter Pylori strain SS1 14 days prior to harvest, and furthermore these last 5 were also treated with R-alpha-Methylhistamine through oral gavage at 13, 10, and 7 days prior to harvest. 15 mice total.

Surface mucous-producing epithelial cells were collected from the mice using laser microdissection and pressure catapulting (LMPC) with a PALM MicroBeam (Carl Zeiss, Oberkochen, Germany) at CCI (Centre for Cellular Imaging, Sahlgrenska Academy, Gothenburg, Sweden).

Libraries were prepared with SMARTer Total Stranded RNA-seq, Pico input mammalian - V3 (Takara Bio, Kusatsu, Japan). The sample from one mouse in the infected/non-treated group failed library prep.

The remaining 14 samples were sequenced with NovaSeq 6000 (Illumina, San Diego, USA at NGI (National Genomics Infrastructure, Solna, Sweden).

The fastq-files were processed with the nf-core/rnaseq analysis pipeline, which was was run by NGI at UPPMAX (Uppsala Multidisciplinary Center for Advanced Computational Science, Uppsala, Sweden).

The files follow the standard NGI distribution packaging, except for the folder structures 00-Reports/ and 01-RNA-Results/ which have been packaged as zip files for easier downloading.

Denna RNA-sekvenserings (RNAseq)-data kommer från slemproducerande epitelceller i magsäcken från C57/BL6-möss.

5 möss var icke-infekterade kontroller, 5 var infekterade med Helicobacter Pylori-stammen SS1 14 dagar före skörd, och ytterligare 5 var också infekterade med Helicobacter Pylori-stammen SS1 14 dagar före skörd, samt dessutom behandlades dessa sista 5 med oralt R-alfa-Metylhistamin 13, 10 och 7 dagar före skörd. Totalt 15 möss skördades.

Ytliga slemproducerande epitelceller samlades in från mössen med laseravskiljning och tryckkatapult (LMPC) med en PALM MicroBeam (Carl Zeiss, Oberkochen, Tyskland) vid CCI (Center för Cellulär Avbildning, Sahlgrenska Akademin, Göteborg, Sverige).

Library prep utfördes med kitet SMARTer Total Stranded RNA-seq, Pico input mammalian - V3 (Takara Bio, Kusatsu, Japan). Library prep för provet från en mus i den infekterade/icke-behandlade gruppen misslyckades.

De återstående 14 proverna sekvenserades med NovaSeq 6000 (Illumina, San Diego, USA) vid NGI (National Genomics Infrastructure, Solna, Sverige).

Fastq-filerna bearbetades med nf-core/rnaseq-analyspipelinen, som kördes av NGI vid UPPMAX (Uppsala Multidisciplinary Center for Advanced Computational Science, Uppsala, Sverige).

Filerna är packade enligt NGIs standard för distribution, förutom mappstrukturerna 00-Reports/ och 01-RNA-Results/ vilka har blivit packade som zip-filer för att underlätta nedladdning.
RNA-sekvensering av slemproducerande celler som med hjälp av laserbaserad mikrodissektion hämtats från musmagsäckar som är infekterade med Helicobacter pylori-stammen Sydney Strain 1
RNAseq of foveolar cells from H. pylori infected mouse stomachs, with or without treatment with R-alpha-Methylhistamine
Keywords: Epithelial Cells; Epitelceller; Gastric Mucins; Magmuciner; Gastric Mucosa; Magslemhinna; Methylhistamines; Metylhistaminer; Mice, Inbred C57BL; Möss, inavlade C57BL; Mucins; Muciner; Mucus; Slem; Gene Expression; Genuttryck; Helicobacter pylori; Helicobacter pylori; Helicobacter Infections; Helicobacterinfektioner; Sequence Analysis, RNA; RNA-sekvensanalys; Gene Expression Profiling; Genuttrycksprofilering; Laser Capture Microdissection; Lasermikrodissektion; Helicobacter pylori [H.pylori] as the cause of diseases classified to other chapters; Helicobacter pylori [H.pylori] som orsak till sjukdomar som klassificeras på annan plats; laser microdissection and pressure catapulting (LMPC); laserbaserad mikrodissektion; Foveolar cells; ytliga slemproducerande magsäckssceller; Gastric surface mucous cells; Ytliga slemproducerande magsäckssceller; Medication and treatment; Medicinering och behandlingar; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi); Cell Biology; Cellbiologi; Immunology; Immunologi; Microbiology; Mikrobiologi; Bioinformatics and Computational Biology; Bioinformatik och beräkningsbiologi; Signs and symptoms; pathological conditions; Tecken och symtom; patologiska tillstånd; Public health; Folkhälsa; Molecular Biology; Molekylärbiologi